Identification of dual-active sites in cobalt phthalocyanine for electrochemical carbon dioxide reduction. (January 2020) - Xia, Yujian; Kashtanov, Stepan; Yu, Pengfei; Chang, Lo-Yueh; Feng, Kun; Zhong, Jun; Guo, Jinghua; Sun, Xuhui
Abstract: Cobalt phthalocyanine (CoPc) as a typical transition metal complex catalyst for electrochemical CO2 reduction is able to produce CO with high selectivity and activity. However, the reaction mechanism remain unclear because of the ambiguity in catalytic active sites between Co center atom and Pc ligand. Herein, synchrotron-based X-ray photoelectron spectroscopy (XPS) and soft X-ray absorption spectroscopy (XAS) were employed to elucidate the catalytic active site evolution during the reaction process. We found that the electrochemical reduction reaction of CO2 on CoPc follows a dual-active sites process. The CO2 molecule is initially protonated on the N atom site of Pc ligand forming *COOH intermediate and then is further reduced to *CO at the center Co site. Graphical abstract: Image 1 Highlights: Cobalt phthalocyanine under electrochemical CO2 reduction conditions was studied by synchrotron-based XPS and XAS. The electrochemical CO2 reduction on cobalt phthalocyanine is a dual-reactive sites reaction process. CO2 is protonated on N site of cobalt phthalocyanine at open-circuit voltage forming *COOH. The formed *COOH is transferred to Co and then reduced to *CO under applied voltage.